2020
DOI: 10.3390/ijerph17165940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Reported Medication Adherence with Potentially Inappropriate Medications in Elderly Patients: A Cross-Sectional Pilot Study

Abstract: Background: Polypharmacy (PP) and potentially inappropriate medications (PIMs) cause problematic drug-related issues in elderly patients; however, little is known about the association between medication adherence and PP and PIMs. This study evaluated the association of self-reported medication adherence with PP and PIMs in elderly patients. Methods: A cross-sectional pilot study was conducted using data collected from electronic medical records of 142 self-administering patients aged ≥65 years, excluding emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
6
1
1
Order By: Relevance
“…Only 50% of older patients who suffered from chronic diseases followed the treatment recommendations, and the rate was even lower in Asia, according to the 2013 WHO report [ 29 ]. The medication adherence rate in our study was 68.82%, higher than in similar studies conducted in China and other Asian countries, with reported rates of 32.6–45% [ 13 , 23 , 30 , 31 ]. The differences are related to the study population and the adherence assessment tools.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Only 50% of older patients who suffered from chronic diseases followed the treatment recommendations, and the rate was even lower in Asia, according to the 2013 WHO report [ 29 ]. The medication adherence rate in our study was 68.82%, higher than in similar studies conducted in China and other Asian countries, with reported rates of 32.6–45% [ 13 , 23 , 30 , 31 ]. The differences are related to the study population and the adherence assessment tools.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the results of this study indicate the opposite. A Japanese study showed that the use of PIM by older patients was significantly associated with self-reported medication adherence [ 23 ]. The reason may be related to the study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the median VAS score was 99%, which was high and similar to the results of previous studies which used VAS to evaluate medication adherence among Japanese elderly. 17) However, there is a possibility that these results may be overestimated because of the variation between subjective and objective evaluations. 18,19) The cut-oŠ point for medication adherence using VAS was 80 100% in previous studies 17,20 25) and is generally 80%; however, this threshold is not always appropriate as it has been arbitrarily deˆned 26) and varies for diŠerent diseases.…”
Section: Discussionmentioning
confidence: 99%